An experimental study on the bond strength between reinforcement bars and concrete as a function of concrete cover, strength and corrosion level - Yalçıner, Hakan; Eren, Özgür; Şensoy, Serhan (Elsevier, 2012)
The effect of corrosion on the bond strength between reinforcement bars and concrete was studied in a series of experiments. An accelerated corrosion method was used to corrode the reinforcement bars embedded in concrete specimens. Pullout tests were performed to develop an empirical model for the ultimate bond strength by evaluating bond strengths in two different concrete mixes, three concrete cover depths and different mass losses of reinforcement bars after corrosion. Bond-slip relationships for the different corrosion levels were compared. It was found that the relationship between bond strength and concrete strength in uncorroded specimens differed from that of corroded specimens set in high-strength concrete because of brittleness in the corroded specimens, which caused a sudden loss of bond strength. The results revealed that specimens with higher concrete strength levels and corroded reinforcements showed a higher percentage of bond strength degradation due to concrete cracking during the pullout tests.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/j.cemconres.2012.01.003) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Corrosion; Pullout test; Bond strength; Bond-slip